Performance analysis of a hybrid optical amplifier based 480-Gbps DWDM-FSO system under the effect of different atmospheric conditions - Obaid, Hafiz Muhammad; Ashraf, Shahzad; Asgher Nadeem, Muhammad; Shahid, Hifsa; Akram, Adeel; Zafrullah, Muhammad (Frontiers in Computer Science, 2024)
Free space optical (FSO) systems offer a desirable and affordable way of providing communication services in remote locations. They provide secure wireless transmission without the requirement for licensing and with lower implementation costs. However, due to the impact of atmospheric turbulences on the effectiveness of FSO systems, their implementation faces significant challenges. Dense wavelength division multiplexing (DWDM) has shown promise in addressing the growing bandwidth needs in optical networks. This paper introduces a hybrid optical amplifier based system, combining DWDM and FSO technology. Energy conservation in such a system involves optimizing various aspects to reduce power consumption while maintaining or improving performance. The proposed DWDM-FSO system operates at a rate of 480 Gbps and consists of 12 channels, each capable of transmitting data at 40 Gbps. The system's performance is evaluated and compared by determining the Q-factor and bit error rate (BER) for both the cases when hybrid amplifier is employed and with no hybrid amplifier within the C-band, specifically focusing on wavelengths around 1550 nm. Moreover, the length of the FSO link is increased to assess the corresponding Q-factor and BER. Resultantly, the maximum distance for the FSO link is determined, ensuring that it remains within acceptable Q-factor and BER thresholds. Furthermore, the FSO system's effectiveness is assessed and compared across various atmospheric conditions. The findings reveal that, in clear weather conditions, the FSO system achieves a maximum distance of 510 meters while maintaining satisfactory Q-factor and BER values when not utilizing a hybrid amplifier. However, by integrating a hybrid amplifier, the system's reach significantly extends to 1700 meters under clear weather conditions, still maintaining acceptable Q-factor and BER values.